Encapsulation of Andrographolide in poly(lactide-co-glycolide) Nanoparticles: Formulation Optimization and in vitro Efficacy Studies - Oseni, Bukola A.; Azubuike, Chukwuemeka P.; Okubanjo, Omotunde O.; Igwilo, Cecilia I.; Panyam, Jayanth (Frontiers in Bioengineering and Biotechnology, 2021)
Andrographolide is a potential chemopreventive and chemotherapeutic agent that suffers from poor aqueous solubility. Encapsulation in poly(lactide-co-glycolide) (PLGA) nanoparticles can overcome solubility issues and enable sustained release of the drug, resulting in improved therapeutic efficacy. In this study, andrographolide was encapsulated in PLGA nanoparticles via emulsion solvent evaporation technique. Effect of various formulation parameters including polymer composition, polymer molecular weight, polymer to drug ratio, surfactant concentration and the organic solvent used on nanoparticle properties were investigated. A selected formulation was used to determine the effect of encapsulation in nanoparticles on andrographolide’s in vitro anticancer efficacy. Nanoparticles formulated using a polymer with 85:15 lactide to glycolide ratio and ethyl acetate as the organic solvent was found to be optimal based on average hydrodynamic particle size (135 ± 4.nm) and drug loading (2.6% ± 0.6w/w). This formulation demonstrated sustained release of andrographolide over 48 h and demonstrated significantly greater in vitro anticancer efficacy compared to free drug in a metastatic breast cancer cell line. These results suggest that additional, more in-depth efficacy studies are warranted for the nanoparticle formulation of andrographolide.